INFLUENCE OF LABOUR MIGRATION PROCESSES ON THE QUALITY OF HUMAN CAPITAL OF THE RUSSIAN FEDERATION - Victor M. Volodin; Nadezhda V. Volodina; Inna A. Pitaikina (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Abstract. Objectives The aim of the study is to identify the impact of labour migration processes on the quality of human capital. Methods For researching the methods and forms of migration capital’s impact on the formation of a new quality of human capital, a systematic approach is applied. In order to identify the imbalance in the distribution of labour resources among the regions of the Russian Federation and to assess migration processes, analytical and synthetic as well as statistical and comparative methods were applied. In order to help to visualise the identified economic and statistical dependencies, graphic images are provided. Results The essence of migration processes in the era of economic turbulence is revealed. The main share of labour migrants in the overall structure of migratory flows to the Russian Federation are labour migrants from the CIS countries; the main reasons for this situation are established. The factors of Russia’s high migration attractiveness are identified and the basic migratory process management tasks are defined. Among the main tasks of migration process management are: ensuring the national security of the Russian Federation; preservation, maintenance and improvement of comfort, well-being and quality of life of the Russian Federation population; solving the problems of stability and growth of the permanent population of the Russian Federation; creating conditions for the full satisfaction of the high-quality labour resource needs of the Russian economy, attracting labour migrants from highly developed countries; formation of conditions for the transition to sustainable development based on the introduction of scientific and technological progress and the creation of competitive industries. Conclusion The paper suggests three scenarios for the development of migration processes in Russia: inertial, realistic and optimistic. Improvements in the quality of migration capital can be achieved through the activation of business migration processes, which will positively affect the quality of human capital in general.